(untitled) (Indian Journal of Chemistry (IJC), 2024)
This study examines the synthesis, characterization, computational analysis, and antibacterial activity of chromium (III) complexes with pyrazolone phenylhydrazone ligands. The ligands and their chromium (III) complexes were synthesized and confirmed using various analytical techniques such as 1H-NMR,13C-NMR, mass spectrometry, elemental analysis, infrared spectroscopy, and UV-visible spectroscopy. The characterization of chromium (III) complexes involved elemental analysis, thermogravimetric analysis (TGA/DTG), differential scanning calorimetry (DSC), FAB mass spectrometry, and UV-visible spectroscopy, which validated their structures and properties. Additionally, the electronic properties and reactivity of the ligands and complexes were investigated using DFT with the B3LYP/6-31G (d, p) basis set. The antimicrobial efficacy of the ligands and complexes was tested against Gram-positive and Gram-negative bacteria, revealing significant antibacterial potential. These findings highlight the importance of pyrazolone phenylhydrazone-based chromium (III) complexes and suggest further exploration of their antimicrobial properties.